How deregulation, drought and increasing fire impact Amazonian biodiversity - Feng, Xiao; Merow, Cory; Liu, Zhihua; Park, Daniel S.; Roehrdanz, Patrick R.; Maitner, Brian; Newman, Erica A.; Boyle, Brad L.; Lien, Aaron; Burger, Joseph R.; Pires, Mathias M.; Brando, Paulo M.; et al. (Nature (London), 2021)
Biodiversity contributes to the ecological and climatic stability of the Amazon Basin 1 , 2 , but is increasingly threatened by deforestation and fire 3 , 4 . Here we quantify these impacts over the past two decades using remote-sensing estimates of fire and deforestation and comprehensive range estimates of 11,514 plant species and 3,079 vertebrate species in the Amazon. Deforestation has led to large amounts of habitat loss, and fires further exacerbate this already substantial impact on Amazonian biodiversity. Since 2001, 103,079–189,755 km 2 of Amazon rainforest has been impacted by fires, potentially impacting the ranges of 77.3–85.2% of species that are listed as threatened in this region 5 . The impacts of fire on the ranges of species in Amazonia could be as high as 64%, and greater impacts are typically associated with species that have restricted ranges. We find close associations between forest policy, fire-impacted forest area and their potential impacts on biodiversity. In Brazil, forest policies that were initiated in the mid-2000s corresponded to reduced rates of burning. However, relaxed enforcement of these policies in 2019 has seemingly begun to reverse this trend: approximately 4,253–10,343 km 2 of forest has been impacted by fire, leading to some of the most severe potential impacts on biodiversity since 2009. These results highlight the critical role of policy enforcement in the preservation of biodiversity in the Amazon. Remote-sensing estimates of fires and the estimated geographic ranges of thousands of plant and vertebrate species in the Amazon Basin reveal that fires have impacted the ranges of 77–85% of threatened species over the past two decades.